Long-Term Field Experiments in Forest Research - (:unkn) unknown (Finnish Forest Research Institute, 2008)
These proceedings are based on a meeting of researchers and data managers working with information on long-term forest field experiments within the NoLTFoX network. Six presentations from one session in the meeting form the main content of the publication. Additional short country reports (8) have been added, one for each member country in the network. Network members from Nordic and Baltic countries have been working on a database including general descriptions of experiments according to common concepts, rules and classifications. The information has been made available on the internet at the NoLTFoX website at http://noltfox.metla.fi. An overview of the work and latest improvements to the database content and functionality is presented. Principles, problems and perspectives are included in the overview. The country status reports add to this information. Some outlines for the future can be found. Expansion to new countries is generally supported and suggested. One way of generating climate data for all included experiments is examined. Plans for improving the content and possible inclusion of other types of information are discussed in several articles. Forest Research in Great Britain is a new member in this network and they have recently added a lot of information on their experiments to the database. Their forest experiments, experiences and viewpoints are presented in detail. A large project concerning field experiments has been launched in Ireland (NATFOREX). Aspects of locating, evaluting and restoring field experiments and/or related information are described as essential parts of this project consisting of five different work packages. Through this project Irish forest research will connect to the NoLTFoX network. Most countries/organizations have relied on some kind of domestic database that they use as a base when generating NoLTFoX information. The Latvian and the Swedish Skogforsk versions are presented in separate articles as examples. Some others are mentioned or presented shortly in the country status reports. The information in domestic databases is often more complex compared to NoLTFoX, but the language is often also only domestic and availability may be restricted. Data submitted for public use in NoLTFoX is more general and serves to give database end-users an overall picture of all experiment activities
Keywords: infrastruktuuri; internet; kenttäkoe; metsäntutkimus; tietokanta; database; field experiment; forest research; infrastructure; internet